Strengthening the role of posyandu cadres through green life programs in sustainable development - Fitria Khasanah; Eko Pujiati; Khoirotul Bariyah (Community Empowerment, 2022)
The problem in Bawang Hamlet, Tunggul Wulung Village, Malang City is that due to a lack of funds and human resources expertise, the development of a healthy environment is not optimal. Furthermore, there are no activities that educate the community about the importance of being productive in order to protect the environment. In order to support sustainable development programs, this community service program aims to strengthen the role of posyandu cadres in strengthening healthy and clean-living communities through Green Life. Strengthening socialization to posyandu cadres about reforestation, practicing green behavior by planting TOGA plants, and reading corners to strengthen community literacy are among the methods used to carry out the activity. This program has a positive impact on posyandu cadres, such as increasing knowledge of reforestation and green culture, beautifying the environment around the posyandu with the TOGA plant, and providing a reading corner in the RW hall to encourage residents to enjoy reading.